Fungsi Manajemen Keuangan Pada Perusahaan - Ahmadum Yossy Herfanda (Jurnal Ekonomi dan Bisnis Digital, 2024)
Corporate Financial Management is about theory, according to experts in the field, what is meant by financial management, the history of financial management, functions and roles and duties, and financial activities. Financial management and all company activities related to how the company operates, obtaining funds, using funds and assets in accordance with the company's overall objectives. This paper is motivated by the general public not knowing how to shape company financial management. The ultimate goal of this paper is to create a deeper understanding of financial management in a company.